A graphene/single GaAs nanowire Schottky junction photovoltaic device. Issue 19 (4th May 2018) - Luo, Yanbin; Yan, Xin; Zhang, Jinnan; Li, Bang; Wu, Yao; Lu, Qichao; Jin, Chenxiaoshuai; Zhang, Xia; Ren, Xiaomin
Abstract : A graphene/nanowire Schottky junction is a promising structure for low-cost high-performance optoelectronic devices. Abstract : A graphene/nanowire Schottky junction is a promising structure for low-cost high-performance optoelectronic devices. Here we demonstrate a graphene/single GaAs nanowire Schottky junction photovoltaic device. The Schottky junction is fabricated by covering a single layer graphene onto an n-doped GaAs nanowire. Under 532 nm laser excitation, the device exhibits a high responsivity of 231 mA W −1 and a short response/recover time of 85/118 μs at zero bias. Under AM 1.5 G solar illumination, the device has an open-circuit voltage of 75.0 mV and a short-circuit current density of 425 mA cm −2, yielding a remarkable conversion efficiency of 8.8%. The excellent photovoltaic performance of the device is attributed to the strong built-in electric field in the Schottky junction as well as the transparent property of graphene. The device is promising for self-powered high-speed photodetectors and low-cost high-efficiency solar cells.